An acid-free process to prepare battery grade nickel and cobalt sulfates from complex resources - Qing Zhang; Xiaohong Zheng; Weiguang Lv; Mingming He; Wenyi Yan; Wenfang Gao; Pengge Ning; Hongbin Cao; Zhi Sun (Nature Communications)
Abstract Nickel sulfate is a critical compound for lithium-ion batteries, mainly prepared from nickel sulfide concentrate (NSC). Typically, high-temperature smelting or high-pressure leaching is required to achieve high extraction rates for Ni and Co. Here, we demonstrate an acid-free atmospheric leaching process for effectively processing of NSC using a mechanochemical treatment. When a suitable intermediate phase of the NSC is obtained, the leaching efficiency for Ni and Co can reach 97.4% and 98.8%, respectively, while the main impure element, iron, almost remains in the solid phase. As a consequence, the leaching solution can be easily treated to prepare battery-grade NiSO4. A technoeconomic analysis demonstrates that the acid-free process provides excellent economic advantages, with carbon emissions being reduced by 59.5%. This provides a sustainable alternative for processing complex sulfide resources and is expected to be applied to zinc and copper sulfide concentrates.